Development of a supportive-educative health education intervention for family caregivers of diabetes mellitus patients: a quasi-experimental study - Siti Fatonah; Sulastri Sulastri; Yuniastini Yuniastini (International Journal of Public Health Science (IJPHS), 2026)
Despite growing evidence on family involvement in diabetes management, few studies have developed and tested structured educational programs targeting family caregivers as active companions in resource-limited settings. This study aimed to evaluate the effectiveness of a comprehensive family support education program based on the five pillars of diabetes mellitus (DM) management in enhancing family knowledge and educational support capacity. A quasi-experimental design with non-probability sampling was employed, involving 157 respondents (intervention group: 72; control group: 85). Social support was measured using a modified Diabetes Social Support Questionnaire-Family. Data were analyzed using independent and paired t-tests. The intervention group demonstrated a significant increase in mean educational support scores from 61.81 to 90.85 (mean difference = 29.04; p < 0.001; Cohen's d = 1.82), indicating a large effect size. The control group showed negligible changes. Poor knowledge decreased from 45.8% to 26.39% in the intervention group, while intermediate knowledge increased substantially. The structured family education program produced a large and statistically significant improvement in caregiving capacity. These findings underscore the need for public health policies to integrate family-centered educational interventions into routine diabetes care, particularly in settings with limited healthcare infrastructure, to reduce disease burden and improve patient outcomes.